Psychosocial Functioning, BMI, and Nutritional Behaviors in Women at Cardiovascular Risk - Eisenberg, Khaya N.; Leiter, Elisheva; May, Rivka T.; Reinfeld, Tanya; Zwas, Donna R. (Frontiers in Psychology, 2020)
Psychosocial factors such as depression, anxiety, and stress are associated with increased cardiovascular risk. Health behaviors may play a role in this relationship, as individuals experiencing elevated levels of anxiety, stress, and/or depression may be less likely to engage in risk-reducing behaviors such as diet and exercise. Evidence suggests that this relationship is particularly relevant for women. This study explored the relationship between levels of anxiety, depression, stress, and specific nutrition behaviors in a sample of 187 women at high cardiovascular risk. BMI was explored as a possible moderator of these relationships. Higher levels of depression in patients with high BMI were associated with increased fruit consumption, whereas this was not seen in highly depressed patients with normal BMI. The reverse pattern was seen for consumption of sweet drinks. Anxiety was found to have a complex relationship with consumption of sweetened drinks and white bread, with higher consumption at moderately elevated levels of anxiety and reduced consumption at the highest levels. These relationships were not seen with elevated levels of stress. Possible interpretations of these findings, as well as their implications for lifestyle interventions with this population are discussed. These findings suggest a number of questions for further research.